Method for connecting silicon nitride / nickel-based superalloy by using chemically modified composite brazing filler metal
Through chemical modified composite pupae connecting silicon nitride/nickel -based high -temperature alloy, the problem of reaction limit when adding low expansion coefficient particles is solved, the efficient interface connection is achieved, the residual stress and thermal expansion of the joints are reduced, and the connection intensity is improved. And high temperature resistance.
Patent Information
- Application Number
- CN202411582755.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-07
AI Technical Summary
In the connection method of silicon nitride ceramic/nickel-based high-temperature alloy, when particles with low expansion coefficient are added, the reaction between the particles and the active elements limits the addition amount, which affects the formation of sufficient interface compounds at the ceramic interface, and thus affects the performance of the joint.
The method of using chemical modified composite pupae to connect silicon nitride/nickel -based high -temperature alloys can use surface copper covering treatment of different carbon sources to delay the reaction with the active element TI, thereby increasing the content of low -expanded particles in welds and reducing welding. The heat expansion and residual stress of the sewing increase the connection strength of the joint.
The effective connection of silicon nitride ceramics and nickel -based high -temperature alloys is achieved, reducing the residual stress and thermal expansion of the joints, and improving the connection strength and high temperature resistance of the joint.
Smart Images

Figure CN119368902A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a welding method, in particular to a method for connecting silicon nitride / nickel-based high-temperature alloy by using chemically modified composite brazing filler metal. Background Art
[0002] The large residual stress caused by the mismatch of thermophysical properties between the parent materials in the joints of dissimilar materials is the main problem affecting the connection performance of the joint. Silicon nitride ceramics and nickel-based high-temperature alloys are widely used in the aerospace field as excellent high-temperature materials. The advantages of silicon nitride and nickel-based high-temperature alloys can be comprehensively utilized through connection methods to further explore their application potential. In order to alleviate the residual stress of the joint, common methods include adding low expansion coefficient particles, which can effectively reduce the residual stress of the joint and surface treatment of ceramics. However, the surface treatment of ceramics has the problem of complex and expensive pre-treatment, and the traditional method of adding low expansion coefficient particles is limited by the reaction between the particles and the active elements. The amount of addition affects the formation of sufficient interface compounds at the ceramic interface, thereby affecting the joint performance. Summary of the invention
[0003] The present invention aims to solve the technical problem that when adding low expansion coefficient particles in the current method for connecting silicon nitride ceramics / nickel-based high-temperature alloys, the reaction between the particles and active elements limits the amount of addition, which affects the formation of sufficient interface compounds at the ceramic interface, and provides a method for connecting silicon nitride / nickel-based high-temperature alloys using chemically modified composite brazing filler metals.
[0004] The method for connecting silicon nitride / nickel-based high-temperature alloys using chemically modified composite brazing filler metals of the present invention is carried out according to the following steps:
[0005] 1. Milling copper-plated carbon powder and copper-plated titanium powder at a low speed by a planetary ball mill to obtain a uniformly mixed composite solder; the volume fraction of the copper-plated carbon powder in the composite solder powder is 5% to 25%;
[0006] 2. Clean the surfaces of the base materials nickel-based alloy, MoCu alloy and base material silicon nitride ceramic;
[0007] 3. Using a tablet press, the composite solder prepared in step 1 and the MoCu alloy cleaned in step 2 are respectively tableted, and then a sheet of MoCu alloy is placed between the two sheets of composite solder to form a sandwich structure, and a binder is applied between the layers to obtain an intermediate layer solder;
[0008] Fourth, an intermediate layer brazing filler metal and a cleaned base material silicon nitride ceramic are sequentially arranged on the cleaned base material nickel-based alloy, and a binder is applied between the intermediate layer brazing filler metal and the two base materials to obtain a workpiece to be welded;
[0009] 5. Place the workpiece to be welded assembled in step 4 into a vacuum heating furnace, heat it from room temperature to 300℃~310℃ and keep it warm for 30min~35min to ensure that the binder is completely volatilized; then heat it from 300℃~310℃ to 1000℃~1060℃ and keep it warm for 5min~20min; finally, slowly cool it to 300℃~310℃, and then cool it to room temperature with the furnace to complete the brazing of ceramic and metal; the entire process of step 5 is carried out under vacuum.
[0010] The present invention performs surface copper coating treatment on different carbon sources (carbon particles, diamond powder, carbon fibers and multi-walled carbon nanotubes) to delay the reaction with the active element Ti, thereby increasing the content of low-expansion particles in the weld, making the connecting piece free of obvious microcracks, further reducing the thermal expansion of the weld, reducing the residual stress of the joint, and improving the connection strength of the joint.
[0011] The present invention aims to obtain a ceramic-high temperature alloy joint with a good interface, and adopts a composite brazing material for partial instantaneous liquid phase connection to obtain a silicon nitride ceramic / GH4169 alloy high temperature resistant joint.
[0012] The process of the invention is simple, and direct brazing of ceramic and metal can be achieved without any modification treatment on the surface of the sample to be welded before welding, and effective connection of ceramic and metal can be achieved by adding an intermediate layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is the assembly drawing of the workpiece to be welded in step 4 of test 1;
[0014] Figure 2 is a SEM image of the copper-plated carbon powder described in step 1 of experiment 2;
[0015] Figure 3 is the XRD pattern of the copper-plated carbon powder described in step 1 of experiment 2;
[0016] Figure 4 The XRD pattern of the copper-plated carbon powder described in step 1 of experiment 3;
[0017] Figure 5 This is the SEM photo of the microstructure of the silicon nitride ceramic / GH4169 alloy joint obtained in Experiment 1;
[0018] Figure 6 This is the SEM photograph of the silicon nitride ceramic / GH4169 alloy joint structure obtained in Experiment 2. DETAILED DESCRIPTION
[0019] Specific implementation method 1: This implementation method is a method for connecting silicon nitride / nickel-based high-temperature alloy using chemically modified composite brazing filler metal, which is specifically carried out in the following steps:
[0020] 1. Milling copper-plated carbon powder and copper-plated titanium powder at a low speed by a planetary ball mill to obtain a uniformly mixed composite solder; the volume fraction of the copper-plated carbon powder in the composite solder powder is 5% to 25%;
[0021] 2. Clean the surfaces of the base materials nickel-based alloy, MoCu alloy and base material silicon nitride ceramic;
[0022] 3. Using a tablet press, the composite solder prepared in step 1 and the MoCu alloy cleaned in step 2 are respectively tableted, and then a sheet of MoCu alloy is placed between the two sheets of composite solder to form a sandwich structure, and a binder is applied between the layers to obtain an intermediate layer solder;
[0023] Fourth, an intermediate layer brazing filler metal and a cleaned base material silicon nitride ceramic are sequentially arranged on the cleaned base material nickel-based alloy, and a binder is applied between the intermediate layer brazing filler metal and the two base materials to obtain a workpiece to be welded;
[0024] 5. Place the workpiece to be welded assembled in step 4 into a vacuum heating furnace, heat it from room temperature to 300℃~310℃ and keep it warm for 30min~35min to ensure that the binder is completely volatilized; then heat it from 300℃~310℃ to 1000℃~1060℃ and keep it warm for 5min~20min; finally, slowly cool it to 300℃~310℃, and then cool it to room temperature with the furnace to complete the brazing of ceramic and metal; the entire process of step 5 is carried out under vacuum.
[0025] Specific embodiment 2: This embodiment is different from the specific embodiment 1 in that: the preparation method of the copper-plated titanium powder described in step 1 is as follows:
[0026] 1. Soak the pure titanium powder in a mixture of acetone and anhydrous ethanol, perform ultrasonic cleaning for 10 to 15 minutes to remove grease on the surface of the powder, and then filter and dry the powder in sequence at a drying temperature of 70° C. for 30 minutes; the mass proportion of acetone in the mixture of acetone and anhydrous ethanol is 50%; the particle size of the pure titanium powder is 2000 mesh;
[0027] 2. Dissolve SnCl2 in deionized water, then add NaOH and dilute sulfuric acid solution in sequence, then add the powder dried in step 1 and ultrasonically vibrate for 1 min to 3 min, and finally filter and dry in sequence;
[0028] The dilute sulfuric acid solution is 1 mol / L;
[0029] The mass ratio of SnCl2 to deionized water is (1 g to 5 g): 40 mL;
[0030] The mass ratio of SnCl2 to NaOH is 1:(0.4-10);
[0031] The mass ratio of SnCl2 to the volume ratio of the dilute sulfuric acid solution is 1g:(1mL~20mL);
[0032] The mass ratio of the pure titanium powder described in step 1 to the SnCl2 described in step 2 is 1:(0.4-10);
[0033] 3. Mix the silver-based activator and purified water, and then add them to the dried product in step 2. Ultrasonic mixing for 1 to 5 minutes, followed by suction filtration and drying at 70°C for 30 minutes.
[0034] The silver-based activator is a silver ammonia solution with a concentration of 10 g / L;
[0035] The mass ratio of the silver-based activator to pure water is 1:(1-5);
[0036] The volume ratio of the pure titanium powder described in step 1 to the silver-based activator described in step 3 is 1g:(20mL-25mL);
[0037] Fourth, CuSO4.5H2O, potassium sodium tartrate and EDTA-2Na are added to pure water and mixed and stirred, and then NaOH is added to adjust the solution to a pH of 11.5-12.5, and then placed in a water bath at 70°C-75°C, and formaldehyde solution is added dropwise, and then the product dried in step 3 is added, and heated in a water bath at 70°C-75°C for 5min-6min, the solution changes from dark blue to white, and finally filtered and dried in sequence to obtain copper-plated titanium powder, and the thickness of the copper plating layer is 1μm-5μm;
[0038] The mass fraction of the formaldehyde solution is 37%;
[0039] The volume ratio of the formaldehyde solution to pure water is 1:(25-50);
[0040] The mass ratio of potassium sodium tartrate to CuSO4.5H2O is 1:(1.3-1.5);
[0041] The mass ratio of potassium sodium tartrate to EDTA-2Na is 1:(1-1.5);
[0042] The mass ratio of the potassium sodium tartrate to the volume of pure water is 1g:(25mL-30mL);
[0043] The mass ratio of the pure titanium powder in step 1 to the potassium sodium tartrate in step 4 is 1:(6-12). The rest is the same as the first embodiment.
[0044] Specific implementation method three: This implementation method is different from the specific implementation method one in that: the preparation method of the copper-plated carbon powder described in step one is as follows:
[0045] 1. Soak the carbon source in concentrated sulfuric acid, ultrasonically clean it for 10-15 minutes, and then ultrasonically clean it in deionized water for 10-15 minutes, and then filter and dry it in sequence, the drying temperature is 70°C, and the time is 30 minutes; the concentration of the concentrated sulfuric acid is 18.4 mol / L;
[0046] 2. Dissolve SnCl2 in deionized water, then add NaOH and dilute sulfuric acid solution in sequence, then add the dried product in step 1 and ultrasonically vibrate for 1 min to 3 min, and finally filter and dry in sequence;
[0047] The dilute sulfuric acid solution is 1 mol / L;
[0048] The mass ratio of SnCl2 to deionized water is (1 g to 5 g): 40 mL;
[0049] The mass ratio of SnCl2 to NaOH is 1:(0.4-10);
[0050] The mass ratio of SnCl2 to the volume ratio of the dilute sulfuric acid solution is 1g:(1mL~20mL);
[0051] The mass ratio of the carbon source described in step 1 to the SnCl2 described in step 2 is 1:(0.4-10);
[0052] 3. Mix the silver-based activator and purified water, and then add them to the dried product in step 2. Ultrasonic mixing for 1 to 5 minutes, followed by suction filtration and drying at 70°C for 30 minutes.
[0053] The silver-based activator is a silver ammonia solution with a concentration of 10 g / L;
[0054] The mass ratio of the silver-based activator to pure water is 1:(1-5);
[0055] The mass ratio of the carbon source described in step 1 to the volume ratio of the silver-based activator described in step 3 is 1g:(20mL-25mL);
[0056] Fourth, CuSO4.5H2O, potassium sodium tartrate and EDTA-2Na are added to pure water and mixed and stirred, and then NaOH is added to adjust the solution to a pH of 11.5-12.5, and then placed in a water bath at 70°C-75°C, and formaldehyde solution is added dropwise, and then the product dried in step 3 is added, and heated in a water bath at 70°C-75°C for 5min-6min, the solution changes from dark blue to white, and finally filtered and dried in sequence to obtain copper-plated carbon powder, and the thickness of the copper plating layer is 6μm-9μm;
[0057] The mass fraction of the formaldehyde solution is 37%;
[0058] The volume ratio of the formaldehyde solution to pure water is 1:(25-50);
[0059] The mass ratio of potassium sodium tartrate to CuSO4.5H2O is 1:(1.3-1.5);
[0060] The mass ratio of potassium sodium tartrate to EDTA-2Na is 1:(1-1.5);
[0061] The mass ratio of the potassium sodium tartrate to the volume of pure water is 1g:(25mL-30mL);
[0062] The mass ratio of the carbon source in step 1 to the potassium sodium tartrate in step 4 is 1:(6-12). The rest is the same as the first embodiment.
[0063] Specific embodiment 4: This embodiment is different from specific embodiment 3 in that the carbon source described in step 1 is carbon fiber powder and is a short-diameter carbon fiber with a mesh size of 1000. The rest is the same as specific embodiment 3.
[0064] Specific embodiment 5: This embodiment is different from specific embodiment 3 in that the carbon source described in step 1 is diamond powder with a mesh size of 600. The rest is the same as specific embodiment 3.
[0065] Specific embodiment 6: This embodiment is different from specific embodiment 3 in that the carbon source described in step 1 is a multi-walled carbon nanotube with an outer diameter of 8nm to 15nm and a density of 0.08g / cm 3 . The rest is the same as the third specific implementation method.
[0066] Specific embodiment 7: This embodiment is different from specific embodiment 6 in that the carbon source in step 1 is amorphous carbon with a mesh size of 800. Other aspects are the same as those of specific embodiment 6.
[0067] Specific implementation eight: This implementation is different from specific implementation one in that: the method for surface cleaning of the base material silicon nitride ceramic in step two is as follows: the silicon nitride ceramic block is roughly ground on a 400# diamond grinding disc until the sample surface is flat, and then W3.5 diamond grinding paste is used to grind on a flat glass until there is no obvious wire cutting mark on the silicon nitride welding surface, and then W1 grinding paste is used to grind until the silicon nitride ceramic surface is bright, and finally anhydrous ethanol is used for ultrasonic cleaning for 10 minutes, and dried for use. The rest is the same as specific implementation one.
[0068] Specific embodiment 9: This embodiment is different from specific embodiment 1 in that: in step 2, the method for surface cleaning of the base nickel-based alloy and MoCu alloy is as follows: the base nickel-based alloy and MoCu alloy are treated with water sandpaper to remove the oxide layer and coarse scratches visible to the naked eye on the surface, and then the surfaces of the base nickel-based alloy and MoCu alloy are polished with metallographic sandpapers of No. 600, 800, and 1000 in sequence until there are no obvious scratches, and finally polished with diamond particles with a particle size of 0.5 μm to make the metal connection surface bright. The rest is the same as specific embodiment 1.
[0069] Specific implementation example ten: This implementation example is different from the specific implementation example one in that the adhesive in step three and step four is 502 glue. The rest is the same as the specific implementation example one.
[0070] The present invention is verified by the following tests:
[0071] Test 1: This test is a method for joining silicon nitride / nickel-based high-temperature alloys using chemically modified composite brazing filler metals, which is specifically carried out in the following steps:
[0072] 1. The copper-plated carbon powder and the copper-plated titanium powder are subjected to low-speed ball milling at a rotation speed of 100 r / min by a planetary ball mill to obtain a uniformly mixed composite solder; the volume fraction of the copper-plated carbon powder in the composite solder powder is 20%;
[0073] The preparation method of the copper-plated titanium powder is as follows:
[0074] 1. Soak the pure titanium powder in a mixture of acetone and anhydrous ethanol, perform ultrasonic cleaning for 10 minutes to remove grease on the surface of the powder, and then filter and dry in sequence at a drying temperature of 70°C for 30 minutes; the mass proportion of acetone in the mixture of acetone and anhydrous ethanol is 50%; the particle size of the pure titanium powder is 2000 mesh;
[0075] 2. Dissolve SnCl2 in deionized water, then add NaOH and dilute sulfuric acid solution in sequence, then add the powder dried in step 1 and ultrasonically vibrate for 1 min to 3 min, and finally filter and dry in sequence;
[0076] The dilute sulfuric acid solution is 1 mol / L;
[0077] The mass ratio of SnCl2 to deionized water is 3g:40mL;
[0078] The mass ratio of SnCl2 to NaOH is 1:5;
[0079] The mass ratio of SnCl2 to the volume ratio of the dilute sulfuric acid solution is 1g:10mL;
[0080] The mass ratio of the pure titanium powder described in step 1 to the SnCl2 described in step 2 is 1:5;
[0081] 3. Mix the silver-based activator and purified water, and then add them to the dried product in step 2. Ultrasonic mixing for 4 minutes, followed by suction filtration and drying. The drying temperature is 70°C and the time is 30 minutes.
[0082] The silver-based activator is a silver ammonia solution with a concentration of 10 g / L;
[0083] The mass ratio of the silver-based activator to pure water is 1:3;
[0084] The mass ratio of the pure titanium powder described in step 1 to the volume ratio of the silver-based activator described in step 3 is 1 g:25 mL;
[0085] 4. Add CuSO4.5H2O, sodium potassium tartrate and EDTA-2Na to pure water and mix and stir, then add NaOH to adjust the solution to a pH of 12, then put it in a 75°C water bath, add formaldehyde solution dropwise, then add the dried product in step 3, heat in a 75°C water bath for 6 minutes, the solution changes from dark blue to white, finally filter and dry in sequence to obtain copper-plated titanium powder, the thickness of the copper plating is 5 μm;
[0086] The mass fraction of the formaldehyde solution is 37%;
[0087] The volume ratio of the formaldehyde solution to pure water is 1:50;
[0088] The mass ratio of potassium sodium tartrate to CuSO4.5H2O is 1:1.3;
[0089] The mass ratio of potassium sodium tartrate to EDTA-2Na is 1:1.5;
[0090] The mass ratio of potassium sodium tartrate to pure water is 1 g:25 mL.
[0091] The mass ratio of the pure titanium powder described in step 1 to the potassium sodium tartrate described in step 4 is 1:10.
[0092] The preparation method of the copper-plated carbon powder is as follows:
[0093] ①, soak the carbon source in concentrated sulfuric acid, ultrasonically clean it for 10 minutes, then ultrasonically clean it in deionized water for 10 minutes, and then filter and dry it in turn, the drying temperature is 70°C, and the time is 30 minutes; the concentration of the concentrated sulfuric acid is 18.4 mol / L; the carbon source is carbon fiber powder and it is a short-diameter carbon fiber of 1000 mesh;
[0094] ②, dissolve SnCl2 in deionized water, then add NaOH and dilute sulfuric acid solution in sequence, then add the dried product in step ① and ultrasonically vibrate for 1min to 3min, finally filter and dry in sequence;
[0095] The dilute sulfuric acid solution is 1 mol / L;
[0096] The mass ratio of SnCl2 to deionized water is 5g:40mL;
[0097] The mass ratio of SnCl2 to NaOH is 1:5;
[0098] The mass ratio of SnCl2 to the volume ratio of the dilute sulfuric acid solution is 1g:10mL;
[0099] The mass ratio of the carbon source described in step ① to the SnCl2 described in step ② is 1:5;
[0100] ③, mix the silver-based activator and purified water, and then add them to the dried product in step ②, mix them by ultrasonic for 1 min to 5 min, and then filter and dry them in turn, the drying temperature is 70°C, and the time is 30 min;
[0101] The silver-based activator is a silver ammonia solution with a concentration of 10 g / L;
[0102] The mass ratio of the silver-based activator to pure water is 1:4;
[0103] The mass ratio of the carbon source described in step ① to the volume ratio of the silver-based activator described in step ③ is 1 g:25 mL;
[0104] ④, CuSO4.5H2O, potassium sodium tartrate and EDTA-2Na were added to pure water and mixed and stirred, and then NaOH was added to adjust the solution to a pH of 12, and then placed in a 75°C water bath, and formaldehyde solution was added dropwise, and then the product dried in step ③ was added, and heated in a 75°C water bath for 6 minutes, the solution changed from dark blue to white, and finally filtered and dried in sequence to obtain copper-plated carbon powder, and the thickness of the copper coating was 9 μm;
[0105] The mass fraction of the formaldehyde solution is 37%;
[0106] The volume ratio of the formaldehyde solution to pure water is 1:30;
[0107] The mass ratio of potassium sodium tartrate to CuSO4.5H2O is 1:1.5;
[0108] The mass ratio of potassium sodium tartrate to EDTA-2Na is 1:1.5;
[0109] The mass ratio of the potassium sodium tartrate to the volume of pure water is 1g:30mL;
[0110] The mass ratio of the carbon source described in step ① to the potassium sodium tartrate described in step ④ is 1:10;
[0111] 2. Clean the surface of the base material nickel-based alloy GH4169, MoCu30 alloy and base material silicon nitride ceramic;
[0112] The method for surface cleaning of the base material silicon nitride ceramic is as follows: the silicon nitride ceramic block is coarsely ground on a 400# diamond grinding disc until the sample surface is flat, and then W3.5 diamond grinding paste is used to grind on a flat glass until there is no obvious wire cutting mark on the silicon nitride welding surface, and then W1 grinding paste is used to grind until the surface of the silicon nitride ceramic is bright, and finally anhydrous ethanol is used for ultrasonic cleaning for 10 minutes, and dried for use;
[0113] The method for surface cleaning of the base nickel-based alloy and the MoCu30 alloy is as follows: the oxide layer and the coarse scratches visible to the naked eye are treated on the surface of the base nickel-based alloy and the MoCu30 alloy with water sandpaper, and then the surface of the base nickel-based alloy and the MoCu30 alloy is polished with metallographic sandpaper No. 600, 800, and 1000 in sequence until there are no obvious scratches, and finally polished with diamond particles with a particle size of 0.5 μm to make the metal connection surface bright;
[0114] 3. Use a tablet press to press the composite solder prepared in step 1 and the MoCu30 alloy cleaned in step 2 into tablets respectively, then place a sheet of MoCu30 alloy between the two sheets of composite solder to form a sandwich structure, and apply 502 glue between the layers to obtain an intermediate layer solder;
[0115] Fourth, an intermediate layer brazing filler metal and a cleaned base material silicon nitride ceramic are sequentially arranged on the cleaned base material nickel-based alloy, and 502 glue is coated between the intermediate layer brazing filler metal and the two base materials to obtain a workpiece to be welded;
[0116] 5. Put the workpiece to be welded assembled in step 4 into a vacuum heating furnace, first heat it from room temperature to 300℃ at 10℃ / min and keep it warm for 30min to ensure that the 502 glue is completely volatilized; then heat it from 300℃ to 1020℃ at 10℃ / min and keep it warm for 10min; finally cool it to 300℃ at 5℃ / min, and then cool it to room temperature with the furnace to complete the brazing of ceramic and metal; the whole process of step 5 is carried out under vacuum, and the vacuum degree in the high temperature zone (above 750℃) should be guaranteed to be 1×10 -2 After the connection is completed, there is no obvious microcrack in the silicon nitride ceramic / GH4169 alloy joint, the room temperature shear strength of the joint is 117MPa, and the high temperature shear strength of the joint tested at 800℃ is 72MPa.
[0117] Figure 1 This is the assembly diagram of the workpiece to be welded in step 4 of experiment 1, where 1 is Si3N4 ceramic, 2 is composite brazing filler metal, 3 is MoCu30 alloy, and 4 is nickel-based high-temperature alloy GH4169.
[0118] Test 2: This test is different from Test 1 in that the volume fraction of copper-plated carbon powder in the composite solder powder described in step 1 is 8%, the carbon source is amorphous carbon and is 800 mesh; in step 5, the temperature is increased from 300°C to 1040°C at 10°C / min and kept warm for 5 minutes. The rest is the same as Test 1. After the connection is completed, there is no obvious microcrack in the silicon nitride ceramic / GH4169 alloy joint, the room temperature shear strength of the joint is 69MPa, and the high temperature shear strength of the joint tested at 800°C is 34MPa.
[0119] Test 3: This test is different from Test 1 in that the volume fraction of copper-plated carbon powder in the composite solder powder described in step 1 is 10%, the carbon source is diamond micropowder and is 600 mesh; in step 5, the temperature is increased from 300°C to 1060°C at 10°C / min and kept at this temperature for 5 minutes. The rest is the same as Test 1. After the connection is completed, there is no obvious microcrack in the silicon nitride ceramic / GH4169 alloy joint, and the room temperature shear strength of the joint is 74MPa.
[0120] Experiment 4: The difference between this experiment and experiment 1 is that the volume fraction of copper-plated carbon powder in the composite solder powder described in step 1 is 12%, and the carbon source is multi-walled carbon nanotubes with an outer diameter of 8nm to 15nm and a density of 0.08g / cm 3 In step 5, the temperature was raised from 300°C to 1000°C at 10°C / min and kept at this temperature for 20 minutes. The rest was the same as in experiment 1. After the connection was completed, there was no obvious microcrack in the silicon nitride ceramic / GH4169 alloy joint, and the room temperature shear strength of the joint was 65MPa.
[0121] Figure 2 This is the SEM image of the copper-plated carbon powder described in step 1 of experiment 2. Figure 3This is the XRD diagram of the copper-plated carbon powder described in step 1 of experiment 2. The XRD results show that no impurities are introduced during the copper plating process on the surface of the amorphous carbon powder. The SEM image shows that the copper-plated layer wraps the amorphous carbon powder more evenly, and the chemical copper plating effect is good.
[0122] Figure 4 This is the XRD spectrum of the copper-plated carbon powder described in step 1 of experiment three. The XRD results show that no impurities were introduced during the copper plating process on the surface of the diamond micropowder, and the coating was thick, and the original parent material was not detected.
[0123] Figure 5 The SEM photos of the silicon nitride ceramic / GH4169 alloy joint structure obtained in Experiment 1 are shown in Table 1. Figure 5 The corresponding EDS results, combined with the EDS results and SEM images, show that the joint is well bonded, and the interface reaction layer is thin, about 1.6μm, specifically the TiN+Ti5Si3 layer. The low expansion coefficient granular carbon fiber is evenly distributed inside the weld, and the carbon fiber and the weld are bonded by TiC. The weld also contains a copper-based solid solution and a small amount of dispersed Cu-Ti intermetallic compounds. The network-distributed copper-based solid solution can relieve residual stress through plastic deformation.
[0124] Table 1
[0125]
[0126] Figure 6 Table 2 is the SEM photo of the silicon nitride ceramic / GH4169 alloy joint structure obtained in Experiment 2. Figure 6 The corresponding EDS results show that the joint structure is similar to that of the carbon fiber used in Test 1. The results show that the joint is well bonded, and the amorphous carbon adsorbs the active element Ti to react and form the TiC phase. However, due to the decrease in volume fraction, the ceramic interface reaction layer thickens, the amorphous carbon content in the weld is low, the weld thermal expansion coefficient is still large, and the connection strength is greatly reduced.
[0127] Table 2
[0128]
Claims
1. A method for connecting silicon nitride / nickel-based high-temperature alloys using chemically modified composite brazing filler metals, characterized in that The method of joining silicon nitride / nickel-based high-temperature alloys using chemically modified composite brazing filler metals is carried out in the following steps:
1. Milling copper-plated carbon powder and copper-plated titanium powder at a low speed by a planetary ball mill to obtain a uniformly mixed composite solder; the volume fraction of the copper-plated carbon powder in the composite solder powder is 5% to 25%; 2. Clean the surfaces of the base materials nickel-based alloy, MoCu alloy and base material silicon nitride ceramic; 3. Using a tablet press, the composite solder prepared in step 1 and the MoCu alloy cleaned in step 2 are respectively tableted, and then a sheet of MoCu alloy is placed between the two sheets of composite solder to form a sandwich structure, and a binder is applied between the layers to obtain an intermediate layer solder; Fourth, an intermediate layer brazing filler metal and a cleaned base material silicon nitride ceramic are sequentially arranged on the cleaned base material nickel-based alloy, and a binder is applied between the intermediate layer brazing filler metal and the two base materials to obtain a workpiece to be welded; 5. Place the workpiece to be welded assembled in step 4 into a vacuum heating furnace, heat it from room temperature to 300℃~310℃ and keep it warm for 30min~35min to ensure that the binder is completely volatilized; then heat it from 300℃~310℃ to 1000℃~1060℃ and keep it warm for 5min~20min; finally, slowly cool it to 300℃~310℃, and then cool it to room temperature with the furnace to complete the brazing of ceramic and metal; the entire process of step 5 is carried out under vacuum.
2. A method for connecting silicon nitride / nickel-based high-temperature alloys using chemically modified composite brazing filler metal according to claim 1, characterized in that The preparation method of the copper-plated titanium powder described in step 1 is as follows:
1. Soak the pure titanium powder in a mixture of acetone and anhydrous ethanol, perform ultrasonic cleaning for 10 to 15 minutes to remove grease on the surface of the powder, and then filter and dry the powder in sequence at a drying temperature of 70° C. for 30 minutes; the mass proportion of acetone in the mixture of acetone and anhydrous ethanol is 50%; the particle size of the pure titanium powder is 2000 mesh; 2. Dissolve SnCl2 in deionized water, then add NaOH and dilute sulfuric acid solution in sequence, then add the powder dried in step 1 and ultrasonically vibrate for 1 min to 3 min, and finally filter and dry in sequence; The dilute sulfuric acid solution is 1 mol / L; The mass ratio of SnCl2 to deionized water is (1 g to 5 g): 40 mL; The mass ratio of SnCl2 to NaOH is 1:(0.4-10); The mass ratio of SnCl2 to the volume ratio of the dilute sulfuric acid solution is 1g:(1mL~20mL); The mass ratio of the pure titanium powder described in step 1 to the SnCl2 described in step 2 is 1:(0.4-10); 3. Mix the silver-based activator and purified water, and then add them to the dried product in step 2. Ultrasonic mixing for 1 to 5 minutes, followed by suction filtration and drying at 70°C for 30 minutes. The silver-based activator is a silver ammonia solution with a concentration of 10 g / L; The mass ratio of the silver-based activator to pure water is 1:(1-5); The volume ratio of the pure titanium powder described in step 1 to the silver-based activator described in step 3 is 1g:(20mL-25mL); Fourth, CuSO4.5H2O, potassium sodium tartrate and EDTA-2Na are added to pure water and mixed and stirred, and then NaOH is added to adjust the solution to a pH of 11.5-12.5, and then placed in a water bath at 70°C-75°C, and formaldehyde solution is added dropwise, and then the product dried in step 3 is added, and heated in a water bath at 70°C-75°C for 5min-6min, the solution changes from dark blue to white, and finally filtered and dried in sequence to obtain copper-plated titanium powder, and the thickness of the copper plating layer is 1μm-5μm; The mass fraction of the formaldehyde solution is 37%; The volume ratio of the formaldehyde solution to pure water is 1:(25-50); The mass ratio of potassium sodium tartrate to CuSO4.5H2O is 1:(1.3-1.5); The mass ratio of potassium sodium tartrate to EDTA-2Na is 1:(1-1.5); The mass ratio of the potassium sodium tartrate to the volume of pure water is 1g:(25mL-30mL); The mass ratio of the pure titanium powder described in step 1 to the potassium sodium tartrate described in step 4 is 1:(6-12).
3. The method for connecting silicon nitride / nickel-based high-temperature alloys using chemically modified composite brazing filler metal according to claim 1, characterized in that The preparation method of the copper-plated carbon powder described in step 1 is as follows:
1. Soak the carbon source in concentrated sulfuric acid, ultrasonically clean it for 10-15 minutes, and then ultrasonically clean it in deionized water for 10-15 minutes, and then filter and dry it in sequence, the drying temperature is 70°C, and the time is 30 minutes; the concentration of the concentrated sulfuric acid is 18.4 mol / L; 2. Dissolve SnCl2 in deionized water, then add NaOH and dilute sulfuric acid solution in sequence, then add the dried product in step 1 and ultrasonically vibrate for 1 min to 3 min, and finally filter and dry in sequence; The dilute sulfuric acid solution is 1 mol / L; The mass ratio of SnCl2 to deionized water is (1 g to 5 g): 40 mL; The mass ratio of SnCl2 to NaOH is 1:(0.4-10); The mass ratio of SnCl2 to the volume ratio of the dilute sulfuric acid solution is 1g:(1mL~20mL); The mass ratio of the carbon source described in step 1 to the SnCl2 described in step 2 is 1:(0.4-10); 3. Mix the silver-based activator and purified water, and then add them to the dried product in step 2. Ultrasonic mixing for 1 to 5 minutes, followed by suction filtration and drying at 70°C for 30 minutes. The silver-based activator is a silver ammonia solution with a concentration of 10 g / L; The mass ratio of the silver-based activator to pure water is 1:(1-5); The mass ratio of the carbon source described in step 1 to the volume ratio of the silver-based activator described in step 3 is 1g:(20mL-25mL); Fourth, CuSO4.5H2O, potassium sodium tartrate and EDTA-2Na are added to pure water and mixed and stirred, and then NaOH is added to adjust the solution to a pH of 11.5-12.5, and then placed in a water bath at 70°C-75°C, and formaldehyde solution is added dropwise, and then the product dried in step 3 is added, and heated in a water bath at 70°C-75°C for 5min-6min, the solution changes from dark blue to white, and finally filtered and dried in sequence to obtain copper-plated carbon powder, and the thickness of the copper plating layer is 6μm-9μm; The mass fraction of the formaldehyde solution is 37%; The volume ratio of the formaldehyde solution to pure water is 1:(25-50); The mass ratio of potassium sodium tartrate to CuSO4.5H2O is 1:(1.3-1.5); The mass ratio of potassium sodium tartrate to EDTA-2Na is 1:(1-1.5); The mass ratio of the potassium sodium tartrate to the volume of pure water is 1g:(25mL-30mL); The mass ratio of the carbon source described in step 1 to the potassium sodium tartrate described in step 4 is 1:(6-12).
4. A method for connecting silicon nitride / nickel-based high-temperature alloys using chemically modified composite brazing filler metal according to claim 3, characterized in that The carbon source described in step 1 is carbon fiber powder and is a short-diameter carbon fiber with a mesh size of 1000.
5. The method for connecting silicon nitride / nickel-based high-temperature alloys using chemically modified composite brazing filler metal according to claim 3, characterized in that The carbon source described in step 1 is diamond powder and has a mesh size of 600.
6. The method for connecting silicon nitride / nickel-based high-temperature alloys using chemically modified composite brazing filler metal according to claim 3, characterized in that The carbon source described in step 1 is multi-walled carbon nanotubes with an outer diameter of 8nm to 15nm and a density of 0.08g / cm 3 .
7. The method for connecting silicon nitride / nickel-based high-temperature alloys using chemically modified composite brazing filler metal according to claim 3, characterized in that The carbon source described in step 1 is amorphous carbon and has a mesh size of 800.
8. The method for connecting silicon nitride / nickel-based high-temperature alloys using chemically modified composite brazing filler metal according to claim 1, characterized in that The method for surface cleaning of the base material silicon nitride ceramic in step 2 is as follows: coarsely grind the silicon nitride ceramic block on a 400# diamond grinding disc until the sample surface is flat, then use W3.5 diamond grinding paste to grind on a flat glass until there are no obvious wire cutting marks on the silicon nitride welding surface, then use W1 grinding paste to grind until the surface of the silicon nitride ceramic is bright, and finally use anhydrous ethanol ultrasonic cleaning for 10 minutes, and dry for use.
9. The method for connecting silicon nitride / nickel-based high-temperature alloys using chemically modified composite brazing filler metal according to claim 1, characterized in that The method for surface cleaning of the base nickel-based alloy and the MoCu alloy in step 2 is as follows: the base nickel-based alloy and the MoCu alloy are treated with water sandpaper to remove the oxide layer and coarse scratches visible to the naked eye on the surface, and then the surfaces of the base nickel-based alloy and the MoCu alloy are polished with 600, 800, and 1000 metallographic sandpapers in sequence until there are no obvious scratches, and finally polished with diamond particles with a particle size of 0.5 μm to make the metal connection surface bright.
10. The method for connecting silicon nitride / nickel-based high-temperature alloys using chemically modified composite brazing filler metal according to claim 1, characterized in that The adhesive described in step 3 and step 4 is 502 glue.
Citation Information
Patent Citations
Induction brazing welding method for metal part
CN102909449A
Composite type polymer thermistor
CN103594215A
Middle layer assembly and method for connecting Si3N4 ceramic
CN103752973A
Method for ultrasonic-assisted welding of high-temperature material under atmosphere protection
CN112059397A
Indirect brazing method for aluminum nitride ceramic copper-clad plate
CN113307647A